Observatorio de la vivienda urbana en Manizales, Caldas Arteaga Gustavo : parámetros de interés constructivos - Arteaga Botero, Gustavo Adolfo (Ciudad Autónoma de Buenos Aires : Diseño, 2021)
The author addresses, in an original way and with a recognized methodological rigor, the study of the constructive conditions of urban housing that was promoted in the city of Manizales (central western Colombia) in a time frame of five years, making use of the so-called data mining. Overcoming the views that on the house put their focus of interest in purely typological aspects or execution of work, the author manages here to establish quantitative indicators that clearly relate the spatial attributes of the houses analyzed with their most representative technical characteristics: their constructive systems, the forms of the foundation, the interior divisions, the mezzany plates and the roofs, all this without neglecting the aspects of the urban and territorial context on which they are built. Thus, the housing observatory really becomes a good pretext that allows us to understand the complexity of the factors that affect its materialization. But beyond the exemplary treatment of the subject, the research makes a clear call on the importance of democratization in information and its management, which with an adequate translation and visualization must increasingly contribute to citizen participation in decision-making that concerns its built environment.
Marco teórico -- Minería de datos -- Observatorio de la vivienda -- Índices urbanos -- Escenarios de observación -- Escenario constructivo -- Parámetros constructivo -- Conclusiones -- Productos de la investigación.
"El material de esta publicación corresponde a la tesis presentada el 10 de marzo de 2016 en marco de la Maestría en Construcción de la Facultad de Artes (Convenio con sede Manizales) en la Universidad Nacional de Colombia. Acta de grado 1749 del 23 de junio de 2016 (Acta No. 12). Diploma 44368 Reg. No 1755, Folio 17 del libro No. 2.Los jurados designados fueron:Arq. Camilo VillateIng. Diego Alexander EscobarIng. José Fernando Olarte" --Title Page.
Based on the author's thesis (Masters)--Universidad Nacional de Colombia, 2016.
Incluye referencias bibliográficas (páginas 195-200).
En español.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Ciudades y pueblos -- Investigación -- Colombia -- Manizales (Caldas) -- Siglo XXI; Arquitectura doméstico -- Colombia -- Manizales (Caldas) -- Siglo XXI; Manizales (Caldas, Colombia) -- Historia; Libros electrónicos.